Calculation of Aircraft Target's Single-Pulse Detection Probability - Yue,Kuizhi (2015)
ABSTRACT: The original radar cross section data or some rough models are often used to estimate a given aircraft target detection probability. The calculation results may not be very accurate as targets are different from one another and the real radar detection process is complex. A new method for radar cross section model generation is proposed and it takes the random factors like air turbulence into account; this makes it conform to the reality. In addition, this radar cross section model can be directly applied to the radar detection process to calculate the detection probability of a specific aircraft at any attitude. Four typical aerial vehicles are taken as examples to demonstrate this method and information such as detection probability, signal to noise ratio and detection distance. Target's instantaneous probability of being tracked, which corresponds to target's detection probability, can also be calculated. Using these calculation results, we can compare two different aircrafts' stealth performance in detail or optimize an aircraft's flight path.